Residential energy expenditures and the relevance of financial inclusion across location, wealth quintiles and household structures - Martinson Ankrah Twumasi; Frank Adusah-Poku; Alex O. Acheampong; Eric Evans Osei Opoku (Heliyon, 2024)
This paper examines the relative role of financial inclusion in enhancing households’ ability to spend on energy consumption across rural and urban locations. It uses comprehensive household data from Ghana and employs the ordinary least square (OLS) as well as an instrumental variable estimation technique. Endogeneity of financial inclusion is instrumented using distance to the nearest bank. Our findings suggest that a standard deviation increase in financial inclusion contributes to an improvement in residential energy expenditure by 1.2835 standard deviations. This finding is robust to different methods for resolving endogeneity and alternative weighting schemes in the financial inclusion construct. Among the different sources of energy for lighting and cooking, financial inclusion increases expenditure on LPG and electricity more than the others. Financial inclusion increases the ability to spend more on residential energy in urban, poorest, and female-headed dual-parent households. Household net income is a key pathway through which financial inclusion affects residential energy expenditure.